OPTIMIZATION OF THE GEOMETRIC PARAMETERS OF THE CROSS-SECTION OF A HOLLOW-CORE FLOOR SLAB TO CREATE A RANGE OF PRODUCTS MANUFACTURED USING THE FORMLESS MOLDING TECHNOLOGY AND INTENDED FOR CONSTRUCTION IN SEISMIC REGIONS - Barkhayot Boratboy ogli Akhmedov (International Journal of Innovations in Engineering Research and Technology, 2021)
For the possibility of using in the construction of seismic regions of hollow-core slabs without formwork, reinforced with prestressed high-strength wire reinforcement, the problem is solved to determine the optimal combination of geometric parameters of the cross-section of the geometric parameters of the cross-section of such a slab while observing the normalized operational requirements and restrictions of the norms of seismic-resistant construction As a result of the research, a constructive solution for the cross-section of the slab was developed for the maximum values of the parameters specified by the customer - span, operating load. A utility model patent was obtained for the proposed structural solution of the slab section.